Analisis Linguistik Terhadap Kesalahan Berbahasa dalam Karya Jurnalistik Mahasiswa di Media Daring Genta FKIP UNJA - Hilman Yusra; Arum Gati Ningsih; N. Nurfadilah; Ade Bayu Saputra (RETORIKA: Jurnal Ilmu Bahasa, 2026)
This study aims to analyze the forms and factors causing language errors in student journalistic works in the online media Genta FKIP UNJA. The method used is a corpus-based descriptive linguistic analysis using 20 news texts published in 2023–2024 as data sources. Data were analyzed by classifying errors at the levels of spelling, morphology, syntax, and semantics. The results showed that the most dominant errors were in the aspect of spelling, followed by morphology, semantics, and syntax. Errors include capitalization, loanwords, affixation, subject repetition, inappropriate use of conjunctions, ambiguity, redundancy, and the use of metaphorical expressions that are not contextually appropriate. Factors causing errors include a weak understanding of language rules, the influence of spoken language in writing, limited vocabulary, ineffective sentences, and minimal editing processes and journalistic training. The findings of this study indicate that improving the quality of student journalistic writing requires concrete solutions in practical techniques and skill development in language error analysis, the application of standard language rules, and systematic editing. Through these efforts, students are expected to produce news texts that are more accurate, effective, and communicative.